The Effectiveness of Teaching Spiritual Concepts Based on Mention and Prayer on Moral Intelligence and Quality of Attachment in Students - سارا آقابابایی; Fateme Hekmatzade (پژوهشنامه روانشناسی مثبت)
The present study aimed to examine the effectiveness of spiritual concepts training centered around mention and prayer on moral intelligence and attachment quality of students. The research method was quasi-experimental with a pre-test, post-test, and follow-up design (for a period of 3 months) with a control group. The statistical population consisted of fifth-grade elementary school students in Isfahan, Iran during the 2019-2020 academic year. From this statistical population, 30 students were selected with available sampling method and randomly assigned to the experimental and control groups (15 students in each group). The spiritual concepts training was conducted through storytelling (role-playing, drama, etc.) for 8 sessions of 45 minutes for the experimental group, while no intervention was given to the control group. The instruments used included the Child-Parent Attachment Questionnaire (IPPA-R) and the Moral Intelligence Questionnaire (MCI). he aim of this study was to determine the effectiveness of teaching spiritual concepts with a focus on remembrance and prayer on moral intelligence and the quality of attachment in Isfahan's fifth grade elementary students in the academic year 2019 – 2020. The statistical population of this applied research was Isfahan's fifth grade elementary students in the academic year 2019 – 2020 and the method of research was semi-experimental with pre-test-post-test and follow-up with control group. The sampling was done by available method that 30 people were randomly assigned to two groups of 15 people tested and controlled. Teaching spiritual concepts by storytelling (role-playing and drama) and the Gallon and Robinson (2005) Child-Parental Attachment Questionnaire (IPPA-R) and the Link and Kiel (2011) Moral Intelligence Assessment Questionnaire were used for data gathering. Data analysis was performed using analysis of covariance. The results showed that teaching spiritual concepts with the focus of remembrance and prayer had a significant effect with Impact coefficient 0.65 on moral intelligence and with Impact coefficient 0.79 on the quality of students' attachment. Also, this effect has been in the follow-up phase. Research findings showed that teaching spiritual concepts with the focus on remembrance and prayer lead to increasing moral intelligence and improving the quality of attachment to parents in students. Data analysis was performed using covariance analysis. The results indicated that spiritual concepts training centered around mention and prayer had a significant impact on moral intelligence and on the quality of attachment of students at the post-test stage and follow-up stage. IntroductionMoral education is a serious and vital matter for any society. However, the moral education of individuals has been most neglected. This neglect has led to all the disorders occurring on a global scale and the various challenges humanity is grappling with today, stemming from a disregard for moral training and development (Mahoney, 2010).Attachment is another variable in this study. Bowlby (1969) defined attachment as a strong emotional bond between two individuals, in which one strives to act in a way that preserves the relationship and maintains its continuity (Golbandihaghighat, 2011). Some studies indicate that insecure attachment is associated with lower levels of spirituality (Hiebler et al., 2016).Spirituality in children encompasses their connection with themselves, the external world, and their understanding of purpose and meaning in life (Westerlund, 2016; Leitao et al., 2023). Children’s spiritual development is shaped by the interplay between their sense of self, interactions with others, and their surrounding world. It is through these daily experiences that children’s spirituality becomes evident (Rouse & Hyde, 2024).A longitudinal randomized controlled trial involving 1769 children across different countries found that spiritual interventions increased happiness and psychological well-being in children (Pandya, 2017). Kobak et al. (2005) found that attachment to parents and moral values play a fundamental role in the lives of children aged 6–12 years. Additionally, teaching spirituality, by connecting with children’s innate nature and gentle spirit and stimulating their empathetic traits, leads to positive outcomes. Similarly, Walker and Moon (2011) conducted a case study on a 14-year-old boy in the United States who exhibited symptoms of generalized anxiety disorder. They found that a spiritual intervention through prayer reduced the boy’s anxiety symptoms, suggesting that prayer can be therapeutic.However, a review of previous research revealed no studies that specifically investigated the impact of teaching spiritual concepts centered on zikr (remembrance) and prayer on moral intelligence and attachment quality. Furthermore, few studies have explored teaching spiritual concepts with an emphasis on zikr and prayer in children. Therefore, given the importance of moral intelligence and attachment quality, this study aimed to investigate the effectiveness of teaching spiritual concepts centered on zikr and prayer on these aspects in students.MethodThis study employed a quasi-experimental design with a pretest-posttest and follow-up framework, including a control group. The statistical population consisted of all fifth-grade elementary students in Isfahan, Iran during the 2019-2020 academic year. The sample included 30 fifth-grade students from Sajad Elementary School in District 2 of Isfahan, selected through convenience sampling. These 30 students were randomly assigned to two groups of 15, an experimental group and a control group. The data collection tools included the Moral Competence Inventory (MCI) and the Inventory of Parent and Peer Attachment (IPPA). After sample selection, the participants in the experimental group attended eight 45-minute sessions of spiritual concept training. These sessions were conducted in-person at a counseling center with the experimental group students. Following the completion of the training sessions, a posttest was administered, and a follow-up assessment was conducted three months later.The training on spiritual concepts involved storytelling, role-playing, and theatrical performances that conveyed moral intelligence concepts such as kindness, respect, and patience. For each topic, materials were provided that emphasized zikr (remembrance) and prayer. Zikr and prayer were used as techniques to reinforce the discussed topics in the students.Steps for Designing the Spiritual Concepts Training Package1.Review of Existing ResourcesThe following resources were studied to inform the intervention:Sweet Tales of Tazkirat al-Awliya (Alar, 2013).Life is Calling You (Safaeian, 2014) .Flight to Infinity (Ghazi Mirsaiid et al, 2014) .Exploring the Role of Prayer in Physical and Mental Health (Azhdar et al, 2011) .Spiritual Interventions in Child and Adolescent Psychotherapy (Walker & Hathaway, 2012/2017).Development of the Training Package:Based on the review of these resources, a comprehensive training package was designedInitial Implementation:The training package was tested on three students in a preliminary phaseExpert Feedback:Feedback was gathered from psychology experts using the Content Validity Ratio (CVR) and Content Validity Index (CVI).Implementation of the Intervention:The finalized training package was applied to the experimental and control groups for assessmentResultsThe data from this study were analyzed in two stages: descriptive and inferential statistics. In the descriptive stage, the means and standard deviations were calculated, while in the inferential analyses, the analysis of covariance (ANCOVA) was employed.To test the assumption of normality in score distribution, the Kolmogorov-Smirnov test and Levene’s test were used. The null hypothesis for normal distribution of scores in both groups across all dependent variables was confirmed, validating the assumption of normality for both groups (p≥0.05).The results indicated a significant difference in moral intelligence scores between the experimental and control groups in the post-test and follow-up stages (p ≤ 0.01). This confirms the effectiveness of teaching spiritual concepts centered on zikr and prayer in improving moral intelligence among fifth-grade students in Isfahan.The effect size for moral intelligence was 0.65 in the post-test stage and 0.45 in the follow-up stage. This means that 65% and 45% of the total variance in moral intelligence scores were attributable to group membership.The results of univariate ANCOVA for attachment quality scores also revealed a significant difference between the experimental and control groups in the post-test and follow-up stages (p ≤ 0.01). This confirms the effectiveness of teaching spiritual concepts centered on zikr and prayer in improving attachment quality among fifth-grade students.The effect size for attachment quality was 0.79 in the post-test stage and 0.38 in the follow-up stage. This indicates that 79% and 38% of the total variance in attachment quality scores were attributable to group membership.ConclusionThis study aimed to determine the effectiveness of teaching spiritual concepts centered on zikr (remembrance) and prayer on the moral intelligence and attachment quality of fifth-grade students in Isfahan, Iran. The results showed that such spiritual training led to an increase in moral intelligence and improved attachment quality with parents.Attachment to parents and moral values plays a fundamental role in the lives of children aged 6-12 years. Spiritual education, by resonating with the innate sensitivity of children and stimulating their empathetic capacities, can yield positive impacts, including enhanced moral intelligence (Kobak et al., 2005). Additionally, spiritual interventions have been shown to increase happiness and improve psychological well-being in children (Pandya, 2017).The link between moral intelligence and spirituality can be understood by recognizing the protective role of ethical and spiritual principles in everyday life. Strengthening the spiritual dimension—such as self-awareness, patience, respect for others, and fostering optimistic and positive attitudes—can significantly enhance moral intelligence.Attachment quality, especially with parents, reflects the nature of the child’s emotional bond with their mother. Secure attachment is nurtured when mothers establish close and trusting relationships with their children. Such children learn to trust others and openly express their emotions, enabling them to handle life challenges with resilience. In contrast, insecurely attached children are less likely to engage in meaningful interactions, leading to weaker coping skills in stressful situations Spiritual beliefs and practices, such as zikr and prayer, provide individuals with a framework to find meaning in life’s inevitable losses and stresses. This sense of meaning fosters hope and optimism. Consequently, spiritual practices enhance secure attachment by cultivating adaptability and fostering trust and communication, both of which are critical components of attachment.This study has some limitations. For example, this study was conducted in Isfahan, Iran and is limited to a specific age group and gender (fifth-grade girls). Therefore, it is recommended that future studies replicate the study in other contexts and with diverse age and gender groups. Finally, the authors suggest that researchers and practitioners incorporate teaching spiritual concepts through storytelling and role-playing into school curriculums and include these methods in therapeutic programs for children and adolescents to promote moral and emotional development.Ethical ConsiderationsCompliance with Ethical Guidelines: We strictly observed all ethical considerations during the research process. It included ensuring the confidentiality of participants' identities and obtaining informed consent from all participants.Author Contributions: All authors contributed to the study. Both authors conducted the training and co-wrote the article.Conflict of Interest: The authors declare no conflict of interest for this study.Funding: The authors received no financial support for the study.Acknowledgments: The authors would like to thank all participants for their time and participation in this study. *. Corresponding author